2022
DOI: 10.1108/mf-05-2022-0242
|View full text |Cite
|
Sign up to set email alerts
|

Does the gender of board members influence the choice of sustainability report format of listed firms? Empirical evidence from India

Abstract: PurposeThis study examines the effect of gender board characteristics on the choice of sustainability report format in India. A sustainability report covers the environmental and social impacts of firms. It is presented either as an integrated report with the rest of the financial reporting to stakeholders or a separate document (stand-alone) with the advantage of communicating better information.Design/methodology/approachThe study uses an inclusive sample of 800 firm-year observations between 2010 and 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Moreover, García-S anchez (2020) found that larger boards increase the quality of MEDAR 32,2 CSRA. However, other studies have found no connection between CSRA and board size (Oware et al, 2022;Miras-Rodriguez and Di Pietra, 2018;Kend, 2015).…”
Section: The Need For Corporate Social Responsibility Reporting and A...mentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, García-S anchez (2020) found that larger boards increase the quality of MEDAR 32,2 CSRA. However, other studies have found no connection between CSRA and board size (Oware et al, 2022;Miras-Rodriguez and Di Pietra, 2018;Kend, 2015).…”
Section: The Need For Corporate Social Responsibility Reporting and A...mentioning
confidence: 81%
“…This result suggests that implementing a bundling effect by combining independent directors with other board variables will lead to better CSRA implementation. However, Aladwey et al (2022) and Oware et al (2022) indicate an insignificant relationship between board independence and the adoption of CSRA.…”
Section: The Need For Corporate Social Responsibility Reporting and A...mentioning
confidence: 95%
“…Thus, this dataset is helpful for the regulations and legal authorities in encouraging women's participation, especially in high-polluting industries like the energy sector. Additionally, women in higher positions and who have diverse expertise and experience, especially in energy-related companies, tend to improve firms' governance and ethical dimension [15 , 16] especially promoting CID [16] . Even with WD representation with other industry differences, multiple directorships, experiences, background, external connections, and professional expertise can influence their perspectives and viewpoints in enhancing CID, WDs participations in the energy sector remain a problem [17] .…”
Section: Objectivementioning
confidence: 99%
“…Even with WD representation with other industry differences, multiple directorships, experiences, background, external connections, and professional expertise can influence their perspectives and viewpoints in enhancing CID, WDs participations in the energy sector remain a problem [17] . Therefore, by using this dataset, it may encourage the regulators and governments to emphasize the policy of WDs' involvement in corporate world as little enforcement and low law abiding especially in emerging economies [15] including in the energy sector. The dataset also may improve the gender diversity and carbon emissions literature as they are scarce and contradictory [18] , [19] , [20] , [21] , [22] .…”
Section: Objectivementioning
confidence: 99%